Malaysian acquiring firms’ shareholders’ wealth effect following cross-border acquisition - Uddin, Md Mohan; Minai, Mohd Sobri; Olajide, Raji Jimoh; Ibrahim, Yusnidah; Hasan, Md Mahadi (CSRC Publishing, 2017)
Purpose: The purpose of this study is to investigate long run shareholders' wealth effect (SWE) of Malaysian acquiring firms following cross-border acquisition (CBA).Methodology: Using buy-and-hold abnormal returns (BHAR) measure of SWE and Euclidean distance method for identifying matching firms, the study investigated 176 CBA deals of Malaysian acquiring firms for the years 2004-2015. Both parametric tests (such as conventional t-statistics, skewness adjusted t-statistics, bootstrapping skewness adjusted t-statistics and Multivariate of Analysis of Variance) and non-parametric statistical (such as Wilcoxon-Mann-Whitney test) tools were employed to analyze the data and test the hypotheses regarding the impact of CBA deals on acquiring firms' SWE.Results: The research found that the SWE of acquiring firms is significantly positive in the shorter period while negative or mixed in the longer period. Furthermore, SWE is found to be different across several groups: (i) Shariah-complaint status firms vs. conventional firms (ii) level of control in target firm (such as major vs. minor acquisitions), (iii) Diversifying acquisition (for example, related vs unrelated acquisition). However, SWE does not differ from industry to industry.Implications: This research presents unique empirical evidences related to long run SWE of Malaysian acquiring firms following CBA. The findings imply that CBA is more success in the longer period.